PERLINDUNGAN HAK PEKERJA PADA STUDI KASUS PEMUTUSAN HUBUNGAN KERJA SEPIHAK - CENDEKIA Jaya, Pengelola Jurnal (CENDEKIA Jaya, 2025)
Protection of workers' rights is a very important issue in the world of work. Especially in the case of unilateral termination of employment. The purpose of this study is to analyse the legal aspects and social impacts of unilateral termination of employment on workers in Indonesia. The action is often carried out without clear reasons or not following established procedures. In this study, we identify various factors that contribute to the occurrence of unilateral layoffs, including the economic situation of the company, pressure from company management, and employees' lack of awareness of their rights. In addition, this research revealed that many employees are unaware of what legal action can be taken against unilateral termination, so they often feel pressurised to accept the decision. This results in unfairness that harms workers and creates insecurity in the labour market.